The Role of Nutritional Supplementation in Hypothyroidism: A Review - Jakub Chodkowski (Quality in Sport)
Introduction: Hypothyroidism is a common endocrine disorder, which affects metabolism and quality of life and often requires lifelong management. Recent studies suggest that nutritional factors, such as iodine, selenium, zinc, and vitamin D, may play a role in thyroid function and symptom management. This systematic review aims to evaluate the effects of specific nutrients and dietary patterns on hypothyroid outcomes, synthesizing evidence to provide dietary guidance for individuals with hypothyroidism and autoimmune thyroid disorders.